A Torch Against the Night - Tahir, Sabaa; Tahir, Sabaa (New York, New York : Razorbill, an imprint of Penguin Random House, 2016)
Laia and Elias fight their way north to liberate Laias brother from the horrors of Kauf Prison, a mission that is complicated by hunting Empire soldiers, the manipulations of the Commandant, and lingering ghosts from their pasts.
Keywords: Fugitives from justice -- Fiction; Brothers and sisters -- Fiction